The Osteochondroma as a Cause of Ischiofemoral Impingement – First Case Series - Güney, Bunyamin; Doğan, Emrah; Özdemir, Murat Yunus (Acta medica Lituanica, 2021)
Ischiofemoral impingement (ISFI) is the compression of the quadratus femoris muscle resulting from the narrowed distance between the lesser trochanter and the ischial bone. Congenital factors (such as developmental hip dysplasia), positional conditions (such as femoral anteversion), intertrochanteric fractures, osteotomy, and osteoarthritis may lead to the superior and medial displacement of the femur which is causing the ISFI. According to the literature, osteochondroma (OC) is not described among the main etiological factors of ISFI. There is only one case report about the relationship between ISFI and OC. We present two ISFI cases due to OC accompanied by radiological findings. Our patients are 19 and 32 years old. Our article is the first case series on this topic.
Keywords: Ischiofemoral impingement; Osteochondroma; Magnetic resonance; Quadratus femoris muscle impingement